1992
DOI: 10.1210/en.131.1.533
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of V1a and V2 vasopressin receptor messenger ribonucleic acids in rat liver, kidney, pituitary and brain

Abstract: The hepatic, vascular-type (V1aR) and the renal, antidiuretic-type (V2R) vasopressin receptor cDNAs were recently cloned from rat liver and kidney libraries, respectively. DNA fragments containing the region encoding the putative 5/6 transmembrane loops of these receptors were subcloned, separately, into RNA polymerase promoter-containing vectors from which 35S-labeled sense and antisense riboprobes were synthesized. In situ hybridization histochemistry showed high levels of V1aR transcripts in the liver and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 0 publications
3
45
2
Order By: Relevance
“…There is good evidence, however, that hypoxia and the peptides vasopressin and endothelin, all factors present during ischemia, stimulate activity of the BBB cotransporter. We have found that vasopressin, which is centrally released during ischemia (Dóczi 1993;Landgraf 1992;Ostrowski et al, 1992;Sorensen et al, 1985) and promotes edema formation (Dickinson and Betz, 1992;Dóczi, 1993;Dóczi et al, 1982Dóczi et al, , 1984Hertz et al, 2000;Rosenberg et al, 1990), is also a potent stimulator of the brain microvascular Na-K-Cl cotransporter (O'Donnell et al, 1995a), as is endothelin, which is also released during ischemia (Barone et al, 1994;Kawai et al, 1996bKawai et al, , 1997Spatz et al, 1997). We have shown that vasopressin stimulates the brain endothelial cotransporter by a V1 vasopressin receptor in a manner involving elevation of intracellular [Ca 2+ ] (O'Donnell et al, 1999).…”
Section: Discussionmentioning
confidence: 90%
“…There is good evidence, however, that hypoxia and the peptides vasopressin and endothelin, all factors present during ischemia, stimulate activity of the BBB cotransporter. We have found that vasopressin, which is centrally released during ischemia (Dóczi 1993;Landgraf 1992;Ostrowski et al, 1992;Sorensen et al, 1985) and promotes edema formation (Dickinson and Betz, 1992;Dóczi, 1993;Dóczi et al, 1982Dóczi et al, , 1984Hertz et al, 2000;Rosenberg et al, 1990), is also a potent stimulator of the brain microvascular Na-K-Cl cotransporter (O'Donnell et al, 1995a), as is endothelin, which is also released during ischemia (Barone et al, 1994;Kawai et al, 1996bKawai et al, , 1997Spatz et al, 1997). We have shown that vasopressin stimulates the brain endothelial cotransporter by a V1 vasopressin receptor in a manner involving elevation of intracellular [Ca 2+ ] (O'Donnell et al, 1999).…”
Section: Discussionmentioning
confidence: 90%
“…The antidiuretic effect of vasopressin is mediated by V2R, which belongs to a large family of G proteincoupled receptors (GPCRs) with a typical seven transmembrane helix structure (Bichet 1994), located in the kidney collecting ducts (Ostrowski et al 1992). Continuous or repeated exposure to an agonist promotes desensitization of GPCRs, and the attenuation of the hormonal response in spite of the presence of hormone, through short-and long-term regulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the vasopressin innervation of the septal area has been implicated in thermoregulation, osmoregulation, social mem ory, motor disturbances, and aggressive behavior (see later). Competition studies using nonradioactive vasopressin analogs (Dorsa et al 1988), electrophysiologi cal studies (Raggenbass et al 1988), in situ hybridization studies (Ostrowski et al 1992), and functional studies suggest that vasopressin receptors in this area re semble vasopressor (V1) receptors and not the antidiuretic receptor or the vaso pressin-oxytocin receptor that is found in the hippocampus (Audigier and Barberis 1985).…”
Section: Nonreproductive Functionsmentioning
confidence: 99%